Peningkatan Keseimbangan dan Mencegah Risiko Jatuh pada Lansia melalui Pemeriksaan Berg Balance Scale - Catherine Hermawan Salim; Astrid Komala Dewi; Sarah Geltri Harahap; Ria Efkelin; Wirya Limala Putra; Levina Salsabila; Vincencius Ferrer Enzo Fittipaldi; Agatha Dian Cordiana Habeahan; Sabrina Sabrina; Angelita Nazwara Putra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Objective: to evaluate the effectiveness of the Berg Balance Scale (BBS) examination in improving balance and preventing the risk of falls in the elderly. The elderly are an age group that is vulnerable to decreased body function, one of which is balance disorders that can increase the risk of falls. Falls in the elderly can have serious impacts such as injury, decreased quality of life, and even death. Balance examination and evaluation are very important to prevent the risk of falls. One of the effective and widely used measuring tools is the Berg Balance Scale (BBS), which assesses balance ability through 14 functional activity items. This study aims to evaluate the role of BBS in detecting balance disorders and as a basis for physiotherapy interventions to improve postural stability in the elderly. The results of the study indicate that periodic use of BBS can help identify elderly people with high risk of falls and monitor balance progress after intervention. Thus, BBS is an important tool in fall prevention strategies and improving the quality of life of the elderly. Conclusion: the use of the Berg Balance Scale is not only effective in assessing balance status, but also as a tool for monitoring the results of physiotherapy interventions in the elderly. Periodic use of BBS is recommended as part of a fall prevention program in health care facilities or elderly communities.